Development of Decision Support Applications for Granting Mortgages using the Fuzzy-Weighted Product method - Nadiva Ramandani; Addin Aditya; Febry Eka Purwiantono (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2023)
Kredit Pemilikan Rumah adalah salah satu fasilitas yang diberikan bank atau Lembaga keuangan lainnya. Kredit pemilikan rumah ini biasanya diperuntukkan bagi masyarakat yang kesulitan dalam membeli rumah. Maka dari itu adanya fasilitas ini diharapkan dapat membantu masyarakat dalam membeli rumah secara kredit. Permasalahan yang terjadi adalah seleksi yang dilakukan oleh analis kredit masih dilakukan secara subyektif sehingga terkadang analis kredit masih kesulitan dalam menentukan layak atau tidaknya nasabah tersebut menerima kredit. Tujuan dari penelitian ini adalah membangun sebuah system informasi pendukung keputusan dengan metode Fuzzy-WP guna membantu analis kredit dalam memutuskan pemberian kredit kepemilikan rumah. Hasil implementasi algoritma menunjukkan bahwa Fuzzy-WP yang diterapkan pada sistem telah sesuai dengan perhitungan aslinya serta program aplikasi dapat menampilkan hasil rekomendasi sesuai dengan kriteria yang telah ditetapkan untuk pemberian kredit bagi calon debitur. Home Ownership Credit (KPR) is one of the facilities provided by banks or other financial institutions. These home ownership loans are usually reserved for people who have difficulty buying a home. Therefore, the existence of this facility is expected to assist people in buying houses on credit. The problem that occurs is that the selection made by credit analysts is still carried out subjectively so that sometimes credit analysts still have difficulty determining whether a customer is eligible to receive credit or not. The purpose of this study is to build a decision support information system using the Fuzzy-WP method to assist credit analysts in deciding whether to grant housing loans. The results of the implementation of the algorithm show that the Fuzzy-WP applied to the system is in accordance with the initial calculations and the application program can display recommendation results according to predetermined criteria for granting credit to prospective borrowers.